Seroprevalence and Risk Factors for Toxoplasma gondii Infection in People Living with HIV: A Cross-Sectional Study from Maputo Central Hospital, Mozambique - Manuel L; Comia IR; Miambo RD; Sousa IM; Cuboia N; Carimo A; Massuanganhe SJ; Buene TP; Banze LR; Paraque BP; Nhancupe N; Schooley RT; et al. (Research and Reports in Tropical Medicine, 2025)
Leonardo Manuel,1– 3,* Isac Rodrigues Comia,1– 3,* Regina Daniel Miambo,3,4 Irina M Sousa,3,5 Nelson Cuboia,3,6 Awa Carimo,3,7 Sara Jacob Massuanganhe,3,7 Titos Paulo Buene,2,3 Lucas Raimundo Banze,2,3 Belmiro Paulo Paraque,3,7 Noémia Nhancupe,2,3 Robert T Schooley,8 Gabriela Maria Santos-Gomes,9 Emília Virgínia Noormahomed,2,3,8 Constance A Benson10 1Faculty of Health Sciences, Lúrio University, Nampula, Mozambique; 2Department of Microbiology, Faculty of Medicine, Eduardo Mondlane University, Maputo, Mozambique; 3Mozambique Institute for Health Education and Research (MIHER), Maputo, Mozambique; 4Department of Animal and Public Health, Faculty of Veterinary Medicine, Eduardo Mondlane University, Maputo, Mozambique; 5Department of Biological Sciences, Faculty of Sciences, Eduardo Mondlane University, Maputo, Mozambique; 6Mozambique Ministry of Health, Hospital Rural de Chicumbane, Limpopo, Mozambique; 7Department of Medicine, Maputo Central Hospital, Maputo, Mozambique; 8Department of Medicine, Infectious Disease Division, University of California, San Diego, California, USA; 9Global Health and Tropical Medicine, GHTM, Associate Laboratory in Translation and Innovation Towards Global Health, LA-REAL, Instituto de Higiene E Medicina Tropical, Universidade NOVA de Lisboa, Lisboa, Portugal; 10Department of Medicine, Division of Infectious Diseases and Global Public Health, School of Medicine, University of California, San Diego, California, USA*These authors contributed equally to this workCorrespondence: Emília Virgínia Noormahomed, Department of Microbiology, Faculty of Medicine, Eduardo Mondlane University (UEM), Av. Salvador Allende 702, Maputo, Mozambique, Email enoormahomed@gmail.comBackground: This study aimed to determine the seroprevalence of toxoplasmosis in people living with HIV (PWH) in Maputo, Mozambique, exploring the interactions between HIV/acquired immunodeficiency syndrome (AIDS) and toxoplasmosis, including HIV-related factors such as the World Health Organization (WHO) HIV/AIDS clinical stage, degree of immunosuppression based on CD4+ T-cell count, and associated risk factors. Additionally, it aimed to assess the prevalence of neurological and psychiatric disorders (NPD) among study participants and its possible association with toxoplasmosis seropositivity.Methods: We conducted a descriptive, cross-sectional study of 200 patients aged > 18 years who were admitted to Maputo Central Hospital, Maputo, Mozambique, between March 2020 and October 2021. The participants were recruited by convenience, regardless of the reason for their admission. Sociodemographic and clinical data, such as age, sex, WHO HIV/AIDS stage, and CD4+ T-cell count, were collected. NPD disorders were assessed using the International Classification of Diseases criteria. Venous blood (5 mL) was obtained from each participant to determine anti-Toxoplasma gondii IgM and IgG antibodies using commercial enzyme-linked immunosorbent assay.Results: Participants were aged 18– 72 years, with the majority being female (64%) and unemployed (57%). Overall, 54.5% of patients tested positive for at least one anti-Toxoplasma gondii IgG (52%) or IgM (6.5%). Risk factors for Toxoplasma gondii infection (p < 0.05) were associated with age group 18– 28 years, being male and unemployed. Moreover, 68.5% of the participants had NPD and of those, 65.1% exhibited anti-Toxoplasma antibodies. We found a significant association between anxiety and IgM seropositivity for p = 0.016. Though three out of four participants with positive anti-Toxoplasma gondii IgG had mood disorders, no significant association was found between Toxoplasma gondii infection with mood disorders, nor with other NPD assessed (56% depression, 33% motor disorder, 25.5% psychosis, 17% cognitive impairment, 7.5% mental retardation).Conclusion: Toxoplasmosis may contribute to NPD in PWH patients. Further studies are recommended to better understand the complex interactions between Toxoplasma gondii, NPD disorders, and HIV.Plain Language Summary: Toxoplasmosis is a disease caused by the zoonotic and food-borne parasite, Toxoplasma gondii. It predominantly manifests in immunocompromised individuals, such as those living with human immunodeficiency virus (PWH), causing neurological and psychiatric impairments due to brain infections. The few existing studies in Mozambique on the burden of neurological and psychiatric disorders have not yet assessed the profile of neurological and psychiatric disorders in patients with HIV or the possible role that this parasite might play as a causative agent. The present study revealed that at least 54.5% of PWH were seropositive for Toxoplasma gondii antibodies and 68.5% had neurological and psychiatric disorders. Additionally, the majority (65.1%) of the patients with neurological and psychiatric disorders were seropositive for Toxoplasma gondii antibodies. Our findings highlight the need to screen for this parasite to clarify its role in the etiology of neurological and psychiatric disorders in both PWH and people without HIV for better healthcare delivery and management.Keywords: latent and acute toxoplasmosis, co-infection Toxoplasma gondii and HIV, Toxoplasma gondii IgG, Toxoplasma gondii IgM, toxoplasmosis and neurological and psychiatric disorders, Mozambique